2013
DOI: 10.1155/2013/279505
|View full text |Cite
|
Sign up to set email alerts
|

MMP1, MMP9, and COX2 Expressions in Promonocytes Are Induced by Breast Cancer Cells and Correlate with Collagen Degradation, Transformation-Like Morphological Changes in MCF-10A Acini, and Tumor Aggressiveness

Abstract: Tumor-associated immune cells often lack immune effector activities, and instead they present protumoral functions. To understand how tumors promote this immunological switch, invasive and noninvasive breast cancer cell (BRC) lines were cocultured with a promonocytic cell line in a Matrigel-based 3D system. We hypothesized that if communication exists between tumor and immune cells, coculturing would result in augmented expression of genes associated with tumor malignancy. Upregulation of proteases MMP1 and MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 71 publications
(70 reference statements)
4
37
0
Order By: Relevance
“…Increased levels of MMP9 have been found on M2 macrophages and are induced in promonocytes when co-cultured with breast cancer cells. 23 Together, these genetic changes not only suggest that tumor-adjacent adipose tissue has a heightened anti-inflammatory response when compared with distant fat but also that genes expressed in tumor-adjacent adipose tissue may promote cellular division, angiogenesis, and invasion, thus providing favorable conditions for breast tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of MMP9 have been found on M2 macrophages and are induced in promonocytes when co-cultured with breast cancer cells. 23 Together, these genetic changes not only suggest that tumor-adjacent adipose tissue has a heightened anti-inflammatory response when compared with distant fat but also that genes expressed in tumor-adjacent adipose tissue may promote cellular division, angiogenesis, and invasion, thus providing favorable conditions for breast tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP1, MMP2, and MMP9 are metastatic genes involved in the invasion of tumor cells into underlying epithelium. [39] This is the first report that liquid biopsies from all cancer patients tested express high levels of MMP1, MMP2, and MMP9, providing a potential new avenue for treatment of metastatic cancers by suppression of these genes; however, these results require confirmation and further investigation. PBMC from five normal individual were tested and found to be negative for expression of cancer-related genes.…”
Section: Discussionmentioning
confidence: 86%
“…showed that sulforaphane could downregulate mRNA of MMP families, such as MMP‐7 and ‐14, and reduce the production of pro‐inflammatory cytokines, immunomodulating cytokine and growth factors . Interestingly, previous study showed a relationship between aggressiveness of breast cancer epithelial cells and their ability to instruct immune cells to modify the expression of genes, such as proteases MMP‐1 and ‐9 . Therefore, these studies indirectly explained that screened DEG, such as MMP‐1, may be related to aggression in breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…MMP play an important role in the cancer invasion metastasis, angiogenesis and tumorigenicity, and it was considered as a candidate marker for identification of breast cancer . At the same time, MMP‐1 and cyclooxygenase‐2 were supported in co‐culture conditions by the promoted expression of proteases in the process of collagen degradation …”
Section: Discussionmentioning
confidence: 99%